2018
DOI: 10.1080/21691401.2018.1489823
|View full text |Cite
|
Sign up to set email alerts
|

Nano-encapsulated HHC10 host defense peptide (HDP) reduces the growth of Escherichia coli via multimodal mechanisms

Abstract: The eradication of several pathogenic drug resistant "Superbug" such as Escherichia coli became difficult especially in chronic infections using existing antibiotics due to the emergence of antibiotic resistance. Owing to their unique antibacterial properties, host defense peptides (HDP) have gained significant attention to combat colonization of bacteria. This study aims designing delivery systems for HHC10 peptide to target bacteria inside the cells might be a promising approach by protecting from degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Currently, in vivo studies typically utilise a subcutaneous injection to deliver defensins [ 20 , 98 ] which is less desirable clinically when compared with oral delivery mechanisms [ 102 ]. A novel delivery mechanism is desirable for defensins to address systemic delivery concerns as well as reduce potential toxicities, allowing the defensins to only be exposed to the host cellular environment upon arrival at the target site [ 103 ]. Such a delivery system may aid in increasing the bioavailability of defensins, thus making them an incredibly attractive area of research for the defensin field [ 103 ].…”
Section: Outstanding Limitations To Be Addressedmentioning
confidence: 99%
“…Currently, in vivo studies typically utilise a subcutaneous injection to deliver defensins [ 20 , 98 ] which is less desirable clinically when compared with oral delivery mechanisms [ 102 ]. A novel delivery mechanism is desirable for defensins to address systemic delivery concerns as well as reduce potential toxicities, allowing the defensins to only be exposed to the host cellular environment upon arrival at the target site [ 103 ]. Such a delivery system may aid in increasing the bioavailability of defensins, thus making them an incredibly attractive area of research for the defensin field [ 103 ].…”
Section: Outstanding Limitations To Be Addressedmentioning
confidence: 99%
“…HHC-10 (Lys-Arg-Trp-Trp-Lys-Trp-Ile-Arg-Trp-NH 2 ) and its Har-rich analog ( 4Har HHC-10; Har-Har-Trp-Trp-Har-Trp-Ile-Har-Trp-NH 2 ) are Trp-rich synthetic AMPs with selectivity and excellent activities against various bacterial superbugs in vitro and in vivo . While conserving the activity against bacteria, the presence of Har residue in 4Har HHC-10 may overcome the associated shortcomings with the peptide proteolytic instability. , The short length of these HHC sequences and the presence of multiple charged and Trp residues is presumably responsible for their strong activity . In this regard, Sharma et al suggested membrane disruption as the direct antimicrobial mechanism of HHC-10 activity against E. coli . However, the detailed contributions of peptide concentration, oligomerization state, and morphological characteristics of self-assembled nanostructures of HHC-10, as well as the peptide sensing of the intrinsic curvature of bacterial cytoplasmic phospholipids especially in the context of induction of cell aggregation, have yet to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…26 In this regard, Sharma et al suggested membrane disruption as the direct antimicrobial mechanism of HHC-10 activity against E. coli. 27 However, the detailed contributions of peptide concentration, oligomerization state, and morphological characteristics of self-assembled nanostructures of HHC-10, as well as the peptide sensing of the intrinsic curvature of bacterial cytoplasmic phospholipids especially in the context of induction of cell aggregation, have yet to be considered.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, Gomez et al showed the encapsulation of synthetic AMPs, namely GIBIM-P5S9K (G17) and GAM019 (G19), in PLGA resulted in a 3-fold and 1-fold decrease of the minimum inhibitory concentration to inhibit 50% of bacterial growth (MIC 50 ) of MRSA for G17NPs and G19NPs, respectively; and the MIC 50 of E. coli showed a 2-fold decrease for both formulations 8 h post-treatment [93]. Additionally, Sharma et al demonstrated enhanced in vitro killing of E. coli with PLGA-encapsulated HHC10 in a concentration-dependent manner and higher cellular uptake in mouse macrophages compared with a peptide solution 12 h post-treatment [94]. The bactericidal activity of PLGA-encapsulated HHC10 occurred via multimodal interactions with bacteria, which involved cell-membrane lysis on direct interaction with bacteria, and activation of apoptotic death pathway (cathepsin-B) upon internalization in E. coli-infected cells in vitro.…”
Section: Synthetic Nanoparticles Plga Nanoparticlesmentioning
confidence: 99%